Enhanced actuated strain of titanium dioxide/nitrile-butadiene rubber composite by the biomimetic method1. Issue 80 (2nd September 2015) - Yang, Dan; Huang, Shuo; Wu, Yibo; Ruan, Mengnan; Li, Shuxin; Shang, Yuwei; Cui, Xiuguo; Wang, Yang; Guo, Wenli
<x xml:space="preserve">Abstract</x> An excellent dielectric elastomer was fabricated by incorporating titanium dioxide nano-particles into nitrile-butadiene rubber by a simple dopamine biomimetic method.